IGFBP5 enhances the dentinogenesis potential of dental pulp stem cells via JNK and ErK signalling pathways. (22nd July 2020) - Hao, Junling; Yang, Haoqing; Cao, Yangyang; Zhang, Chen; Fan, Zhipeng
Abstract: Background: Dental stem cell transplantation has become a new method for tooth tissue regeneration. However, its molecular mechanism of the dentinogenic differentiation is still unclear, limited its application. Our previous studies found that insulin‐like growth factor‐binding protein 5 (IGFBP5) can promote the osteogenic differentiation of periodontal ligament stem cells and the regeneration of periodontal tissues. This study aims to clarify the effect and mechanism of IGFBP5 on the dentinogenesis of dental pulp stem cells (DPSCs). Objective and Methods: Lentiviral IGFBP5 shRNA was used to knock‐down of IGFBP5. And recombinant human IGFBP5 protein (rhIGFBP5) was used to treat DPSCs. Alkaline phosphatase (ALP) staining, Alizarin red staining, quantitative calcium analysis, real‐time RT‐PCR and Western Blot were used to detect dentinogenic differentiation markers and related signalling pathways. Transplantation in nude mice was used to detect the dentin regeneration in vivo. Results: Depletion of IGFBP5 inhibited ALP activity and the mineralisation and reduced the expressions of osteo/dentinogenic differentiation markers BSP, DMP‐1 and DSPP in DPSCs. 0.05 ng/mL rhIGFBP5 promoted ALP activity, the mineralisation and the expressions of BSP, DMP‐1 and DSPP in DPSCs. In addition, 0.05 ng/mL rhIGFBP5 could promote DPSC‐mediated dentin‐like tissues formation in vivo. Western blot results showed that IGFBP5 activated JNK and Erk signalling pathways in DPSCs. Furthermore, inhibition of JNK pathway by SP600125, the expression of p‐JNK and p‐Erk was reduced, while inhibition of Erk pathway by PD98059, only p‐Erk expression was decreased. Conclusions: Our results demonstrated that IGFBP5 could promote the dentinogenic differentiation and dentinogenesis potential of DPSCs via JNK and ErK signalling pathways.